(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Due to the high demands placed on finger joint implants, the most common therapy for joint diseases is still the use of silicone spacers or even joint stiffening. For this reason, the Fraunhofer PREPARE project FingerKIt has set itself the goal of developing a new form of therapy in which patient-specific implants are automatically generated that meet the high requirements placed on them. First steps toward achieving this goal are presented in this paper.